Comparative study of the qualitative features of the Lithuanian and Latvian monophthongs - Grigorjevs, Juris; Jaroslavienė, Jurgita (Baltistica, 2015)
In the present article, a comparative study of the spectral characteristics and distinctive qualitative features of monophthongs of the contemporary Baltic Standard languages pronounced in isolation is described. On the one hand vowels pronounced in isolation do not represent a pronunciation in everyday speech, while on the other hand their production is probably the closest to the acoustic and auditory monophthong targets determined by our mental prototypes. This type of production represents natural hyper-articulation and differs from production of the cardinal vowels.Lithuanian and Latvian monophthongs have been studied and compared using the same methods and equipment that permit a reliable comparison of phonetic inventories (quality similarities and differences) of both languages.For this paper recordings of six native Lithuanian and six native Latvian male informants (having faultless articulation) were used (1944 items were selected and analyzed in total). All informants are speakers of standard language. In this study the standard language is considered as a standardized language (generally the most formal version of the language) used for the needs of public life and culture.Reviewing interrelations between vowels of a single language (Lithuanian or Latvian), the mean data acquired in this study is compared with the data of some previous studies. To compare the general tendencies of the relations between Lithuanian and corresponding Latvian long and short monophthongs pronounced in isolation more precisely, the following acoustic parameters (numeric values) were calculated: acuteness (graveness), flatness, compactness, and tenseness.The results of the present study confirm the general tendency that qualitative characteristics of the Lithuanian long and corresponding short vowels differ to a great extent. However the quality of Latvian monophthongs produced in isolation varies very little and statistical analysis of the spectral characteristics shows contradictory results. A comparison of spectral characteristics and registered acoustic parameters (their calculated mean values) proves that the long and especially corresponding short Lithuanian and Latvian vowels vary, though in general vowel interrelations in both language systems are similar; also the mean data acquired in this study for Lithuanian and Latvian speakers show similar tendencies which in general correspond to those acquired in other studies, and vowel classifications follow the same pattern.